2021
DOI: 10.1371/journal.pone.0250472
|View full text |Cite|
|
Sign up to set email alerts
|

A synopsis of Salvatoria McIntosh, 1885 (Annelida: Syllidae: Exogoninae) from Brazilian coastal and oceanic waters

Abstract: We compiled the records for the genus Salvatoria from Brazilian coastal and oceanic habitats, collected by several projects along the years. Here we present 12 species, eight of which already reported–S. breviarticulata comb. nov., S. clavata, S. euritmica, S. heterocirra, S. limbata, S. longiarticulata comb. nov., S. neapolitana and S. cf. nitidula–with comments regarding the confidence of some of these records. We also describe three new species, S. marielleae n. sp. and Salvatoria nitiduloides n. sp., based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Branchiosyllis belchiori Nascimento, Fukuda & Paiva, 2019, B. gozanguinhai Nascimento, Fukuda & Paiva, 2019, B. oculata (Ehlers, 1887, Exogone africana Hartmann-Schröder, 1974, E. breviantennata Hartmann-Schröder, 1959, E. naidinoides Westheide, 1974, E. rocas Nascimento, Fukuda & Paiva, 2020, E. cf. simplex Hartmann-Schröder, 1960, Haplosyllis spongicola (Grube, 1855, Salvatoria marielleae Nascimento, Fukuda & Paiva, 2021, S. ypsiloides Nascimento, Fukuda & Paiva, 2021, Salvatoria sp., Syllis cornuta Rathke, 1843, and S. variegata (Grube, 1855 (Paiva et al 2007;Nascimento et al 2020Nascimento et al , 2021. This study has identified two species new to science, bringing the total to 16.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Branchiosyllis belchiori Nascimento, Fukuda & Paiva, 2019, B. gozanguinhai Nascimento, Fukuda & Paiva, 2019, B. oculata (Ehlers, 1887, Exogone africana Hartmann-Schröder, 1974, E. breviantennata Hartmann-Schröder, 1959, E. naidinoides Westheide, 1974, E. rocas Nascimento, Fukuda & Paiva, 2020, E. cf. simplex Hartmann-Schröder, 1960, Haplosyllis spongicola (Grube, 1855, Salvatoria marielleae Nascimento, Fukuda & Paiva, 2021, S. ypsiloides Nascimento, Fukuda & Paiva, 2021, Salvatoria sp., Syllis cornuta Rathke, 1843, and S. variegata (Grube, 1855 (Paiva et al 2007;Nascimento et al 2020Nascimento et al , 2021. This study has identified two species new to science, bringing the total to 16.…”
Section: Discussionmentioning
confidence: 99%
“…Syllidae is the most speciose family within Annelida and is typically among the richest in faunal surveys. Currently, 155 species of this family are found in Brazilian waters (Nascimento et al 2021), already including the two described here. It is safe to say that the 16 species found so far off Brazilian oceanic islands represent only a small fraction of the actual richness of this family in these habitats.…”
Section: Discussionmentioning
confidence: 99%
“…The most remarkable characteristic of the new species of Salvatoria is that the pharyngeal tooth is located on the anterior margin of the pharynx, and the compound chaetae have elongated blades on the anterior and the midbody parapodia, with both teeth separated, forming a rounded, concave space. The most similar species is S. nitiduloides (Nascimento et al, 2021) from Brazil. In comparison, the pharyngeal tooth in the Egyptian species is more anteriorly located, and the dorso-ventral gradation in the length of blades is less marked than in the Brazilian species (Nascimento et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The most similar species is S. nitiduloides (Nascimento et al, 2021) from Brazil. In comparison, the pharyngeal tooth in the Egyptian species is more anteriorly located, and the dorso-ventral gradation in the length of blades is less marked than in the Brazilian species (Nascimento et al, 2021). Despite that the body shape, the dorsal and the ventral simple chaetae, and the anterior compound chaetae are almost identical; the posterior chaetae of S. aegyptia sp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation